1999
DOI: 10.1128/mcb.19.2.1390
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Determinants of Proteolytic Processing of Aspergillus PacC Transcription Factor Are Remote from the Processing Site, and Processing Occurs in Yeast If pH Signalling Is Bypassed

Abstract: The Aspergillus nidulans transcription factor PacC, which mediates pH regulation, is proteolytically processed to a functional form in response to ambient alkaline pH. The full-length PacC form is unstable in the presence of an operational pH signal transduction pathway, due to processing to the relatively stable short functional form. We have characterized and used an extensive collection of pacC mutations, including a novel class of "neutrality-mimicking" pacC mutations having aspects of both acidity-and alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
144
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(149 citation statements)
references
References 37 publications
2
144
0
3
Order By: Relevance
“…Acidity-, alkalinity-and neutrality-mimicking mutations have been obtained in pacC (17,33,39,83,95,122). This phenotypic heterogeneity reflects the more direct involvement of the pacC product (the key transcription factor, see below) in regulation of gene expression by ambient pH.…”
Section: Formal Genetics Of Ph Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Acidity-, alkalinity-and neutrality-mimicking mutations have been obtained in pacC (17,33,39,83,95,122). This phenotypic heterogeneity reflects the more direct involvement of the pacC product (the key transcription factor, see below) in regulation of gene expression by ambient pH.…”
Section: Formal Genetics Of Ph Regulationmentioning
confidence: 99%
“…Mutational truncations removing between 92 and 412 residues from the C terminus of PacC result in an alkalinity-mimicking (pacC c ) phenotype (83,95,122;Rainbow et al,unpublished), which revealed that the C-terminal region of PacC contains a negative-acting domain that is inactivated in the presence of alkaline-ambient-pH signaling. Single-residue changes involving residues 259, 266, 340, 573, and 579 also lead to an alkalinity-mimicking pacC c phenotype (41,83). The relatively large size of the region in which alkalinity-mimicking mutations can occur accounts for the ease with which they can be selected and for the erroneous proposal (17), based on their high frequency, that they constitute the loss-of-function class.…”
Section: Mutational Analysis Of Paccmentioning
confidence: 99%
See 2 more Smart Citations
“…7, 8, 17 for reviews). The pH-independent proteolytic processing of PacC 53 into PacC 27 is in all likelihood mediated by the proteasome (11,18). The pathway is conserved in Saccharomyces cerevisiae, where the PacC orthologue Rim101p is activated by a single proteolytic step (19), presumably catalyzed by the budding yeast PalB orthologue Rim13p (20,21).…”
mentioning
confidence: 99%